Impact of formal care consumption on informal care use in Europe: What is happening at the beginning of dependency?. Issue 7 (July 2022) - Rapp, Thomas; Ronchetti, Jérome; Sicsic, Jonathan
Highlights: We exploit a European randomised clinical trial, SPRINTT, targeting frail elderly people. We reproduce the eligibility rules in each country for instrumenting formal care. Receive home-based formal care increase the probability of using informal care. Use formal care does not affect the amount of informal care used. The two types of care are complementary at the beginning of the dependency. Abstract: Little is known about care use decisions at the beginning of the disability process, when older people are vulnerable. This article investigates the impact of formal care (FC) consumption on informal care (IC) utilization in Europe in a population of frail older people. We use data from the Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies (SPRINTT) study, which involves a sample of 1515 elderly (70+) people surveyed in 11 European countries. We explore the impact of home-based FC use on IC use at the extensive and intensive margins. The use of FC is instrumented with a dichotomous variable reproducing the eligibility criteria for public home-based FC in each country. We show that receiving home-based FC positively and significantly affects the probability of using IC. Therefore, we conclude that home-based FC and IC are complementary at the beginning of the dependency process.